Barystatic and steric sea level variations in the Baltic Sea and implications of water exchange with the North Sea in the satellite era - Karimi, Armin Agha; Ghobadi-Far, Khosro; Passaro, Marcello (Frontiers in Marine Science, 2022)
Satellite altimetry, satellite gravimetry, and in-situ subsurface salinity and temperature profiles are used to investigate the total, barystatic, and steric sea level variations in the Baltic Sea, respectively. To estimate steric sea level, the density variations are weighted in deeper layers to prevent overestimation of their contribution. We show that the sum of barystatic and steric components exhibits excellent cross correlation (0.9) with satellite altimetry sea level variations and also explains up to 84% of total signal variability from 2002-to 2019. Considering the dominance of barystatic sea level variations in the basin and limitation of satellite gravimetry in resolving the mass change in water-land transition zones (known as the leakage problem), the mismatch is likely attributed to the inadequate accuracy of the barystatic datasets. The total sea level and its contributors are further decomposed into seasonal, interannual, and decadal components. It is shown that despite its insignificant contributions to seasonal and interannual changes, the steric sea level plays an important role in decadal variations. Additionally, the interannual variations of the barystatic sea level are governed by the North Atlantic Oscillation in the basin. The sea level variation in the North Sea is also examined to deduce the water exchange patterns on different time scales. A drop in the North Sea level can be seen from 2005 to 2011 which is followed by the Baltic Sea level with a ~3-year lag, implying the outflow from the Baltic Sea to the North Sea.